Forming of AISI 409 sheets for fan blade manufacturing - Foroni, Fernando D’Alessio; Moreira Filho, Lindolfo Araujo; Menezes, Miguel Ângelo [UNESP] (Inderscience Publishers, 2008)
The necessity for adapting the standardised fan models to conditions of higher temperature has emerged due to the growth of concerning with the consequences of the Mont Blanc tunnel accident where 41 people died. The objective of this work is to present an alternative to standard fans by considering a new manufacturing procedure for producing fan blades. Experimentation on prototypes combined with circle grid analysis allows concluding that during the sheet metal forming process the zones undergoing more deformation are still below the formability limits and, therefore, the new process can be successful utilised for producing fan blades. © 2008 Inderscience Enterprises Ltd.
Keywords: experimentation; fan blades; sheet-metal forming